Role of Micro RNAs in the Pathogenesis of Rheumatoid Arthritis. Issue 31 (August 2015) - Chen, Xiu-Min; Huang, Qing-Chun; Yang, Sheng-Li; Chu, Yong-Liang; Yan, Yu-Hong; Han, Ling; Huang, Yu; Huang, Run-Yue; Yehuda, Shoenfeld.
<x xml:space="preserve">Abstract</x> Abstract The contributions of micro RNAs (miRNAs) to rheumatoid arthritis (RA) are beginning to be uncovered during the last decade. Many studies in efforts to use miRNAs as biomarkers in disease diagnosis, prognosis, and treatment are ongoing. We conducted a systematic literature review to reveal the role of miRNAs in the pathogenesis of RA in order to inform future research. We analyzed all the literature which is searched by keywords "microRNA" and "arthritis" in PubMed from December 2007 to June 2015, and the references cited by the articles searched were also considered. Relevant literature focusing on the field of miRNAs and RA was identified. The searching process was conducted by 5 independent investigators. The experts in the field of miRNAs and Rheumatology were involved in the process of analyzing. Relevant literature was analyzed according to the objective of this review and the availability of full text. The crucial role of miRNAs in maintaining immune and inflammatory responses is revealed. In addition, it is now clear that miRNAs are implicated in the development of RA synovial phenotype including synovial hyperplasia and joint destruction. Intriguingly, the biomedical application of several miRNAs may result in the effects of "double-edged sword." Moreover, there appears to have a feedback loop for expression of some miRNAs related to disease activity in inflammatory milieu of rheumatoid joint. This review underscores the potential importance of miRNAs to diagnosis, prognosis, and treatment of RA. Further investigations are required to identify the unique miRNAs signatures in RA and characterize the mechanisms mediated by miRNAs in the pathology of RA.